Surprises as a bait to work harder – Four cases in the Louros Archive - Marinis, Christos P. (DELTOS, 2024)
This brief paper discusses the author’s personal impressions from the process of recording, archiving, and categorising the N. Louros Archive during the summer of 2023, as well as the surprises that served as a motivation to continue this effort with increasing enthusiasm. Four cases of primary material with relevant photographs are indicative. Thus, the value of the Louros archive is emphasized for the history of medicine and other scientific fields, encouraging researchers to engage in a fruitful dialogue with related and unrelated sciences. Finally, a brief reference is made to the difficulties encountered during the project.